THE EFFECT OF ELECTRONIC MEDIA ON MUSLIM YOUTH CHARACTER (Study in East Ledong Village, West Ledong Village and Padang Sipirok Village, Aek Ledong District, Asahan Regency) - Kiki Hasibuan (Universitas Dharmawangsa, 2022)
This study aims to describe how the influence of electronic media on the formation of Muslim youth characters in Aek Ledong District, Asahan Regency. This research method is descriptive with a quantitative approach. The results showed that electronic media had an effect on the character formation of Muslim youth in Aek Ledong District. In practice, the influence of electronic media occurs through cellphones in the process of character building. The majority of Muslim youth use mobile phones because they are considered easy in delivery and learning. But besides that, there are still many young people who have difficulty in finding information about character building, so they still need guidance from adults to get used to using electronic media.